QUALITY CHANGES OF SARDINES (Sardinella neopilchardus) AT INDONESIAN AMBIENT TEMPERATURE - Farida Ariyani (Indonesian Journal of Agricultural Science, 2000)
In tropical countries such as Indonesia, high ambient temperature and a lack of icing cause very rapid spoilage of fish. Leaving fish uniced while waiting for processing is a common practice resulting in lower quality of the end products, and consequently lower price of the products. To study the spoilage pattern of sardines (Sardinella neophilchardus) in a tropical region, and to investigate a simple and quick method to judge the degree of spoilage, observations on the deterioration of sardines were carried out by incubating fish in a humidity chamber adjusted to 28-30oC. RH 70-80% for up to 14 h. The changes of sensory attributes based on demerit point score. pH, and total volatile base nitrogen (TVB-N) were monitored to determine the degree of spoilage. Although the appearance of sardines was still bright after 6-h incubation time, fish were not as fresh as those without incubation and the belly and tissue were softened. After incubation time of 10 h, fish showed slight to moderate signs of spoilage with demerit point score of 25 out of the maximum score of 39, and a TVB-N content of 20 mg%N. This is similar to the fish quality commonly used in the commercial production of dried-salted fish in Indonesia. Fish incubated for 12 h or more appeared completely spoiled and were rejected by sensory panel. A high correlation between demerit point score and TVB-N was noted, therefore the demerit point system which was more suitable, quicker, and easier could be used to determine the degree of fish spoilage.